KEGAGALAN KETERWAKILAN PEREMPUAN DI DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN LINGGA TAHUN 2009 - Mafatihul Ulum; Muchid " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Lingga Regency is one of the young regencies in Kepulauan Riau province. After divided into autonomous regions since 2003, the regency has implemented three times Election, which in the 2004, 2009, and 2014. In the 2009, the final result comes with no women are elected as legislators in Lingga regency. It was noted that among of 20 members of the legislature who are not elected members of the legislature with the female gender. The presence of womenn in the legislature considered to be important because it can provide ideas and views that correspond to the presence of women themselves. The absence of women as legislators in Lingga regency is a form of failure of representation for women.This study look at the process (mechanism)of recruitment by political parties in Lingga regency recruit women candidates and to determine the cause of the failure of women's representation in parliament of Lingga regency. The foundation for this research is theory of political recruitment. This study using a qualitative research approach. Based on the analysis, it can be seen that the political recruitment is the estuary of the quality of the proposed candidates. Political recruitment by political parties in the Lingga regency for the candidates is closed recruitment. Closed recruitment has some disadvantage with not involving public to see and assess the ability of elite that displayed.The problem that faced by women in legislative elections in the Lingga regency are low education quality of voters, island regions, and economic factors. Accordance with these results, the failure of women's representation in the Lingga House of Representatives in 2009 due to the closed recruitment by political parties and low quality voters.